Anticancer, antioxidant, and antibacterial activities of the methanolic extract from Sphagneticola trilobata (L.) J. F pruski leaves - Vivi Mardina; Syafruddin Ilyas; Halimatussakdiah Halimatussakdiah; Tisna Harmawan; Masitta Tanjung; Faridah Yusof (Wolters Kluwer Medknow Publications, 2021)
This study aims to investigate the potential of bioactive secondary metabolites contained in Sphagneticola trilobata (L.) J.F Pruski leaves as novel plant-derived anticancer agent. Qualitative bioactive compound contents in the methanolic extract of S. trilobata leaves were screened using phytochemical method. Antioxidant evaluation was carried out using 2,2-diphenyl-1-picrylhydrazyl assay; antibacterial - using well diffusion method on Escherichia coli and Salmonella typhi; and cytotoxicity - using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay on MCF-7 cell line and Vero Cell. It was found that the methanolic extract exhibited antioxidant activity with an IC50 value of 124.34 μg/mL. The inhibition zone values against E. coli and S. thypi (at extract concentration of 100 mg/mL) were 34.33 and 36 mm, respectively. In vitro MTT assay showed that our extract successfully reached 96% mortality with LC50 = 189.287 μg/mL, where the selective index of 2.5 suggest its selectivity against MCF-7 breast cancer cell line. In conclusion, the data of biological activities suggest the potential development of methanolic extract from S. trilobata leaves as a phytomedicine for breast cancer treatment.